The Impact of Social Determinants of Health on Australian Women’s Capacity to Access and Understand Health Information: A Secondary Analysis of the 2022 National Women’s Health Survey - Neve Davison; Karin Stanzel; Karin Hammarberg (Healthcare, 2024)
The ability to access, understand, judge, and use health information is crucial for making informed decisions about health and optimal health outcomes. This secondary data analysis investigated associations between social determinants of health and Australian women’s ability to access and understand health information using data from 10,652 women who responded to the 2022 National Women’s Health Survey. A score (0–5) was created based on five questions assessing the participants’ ability to access and understand health information, which was dichotomised into low (≤3) and high (≥4) scores. The data were analyzed using descriptive statistics, univariate comparisons, and multivariable binary logistic regression. Almost a quarter of the women had a low score. Non-native English speakers were approximately four times more likely to have low health literacy than native English speakers. Additionally, women without tertiary education, financially disadvantaged women, and First Nations women were almost twice as likely to have lower health literacy than other women. These findings suggest that social determinants of health decrease the capacity to access and understand health information. To reduce health inequalities, healthcare systems and health professionals must consider the factors that reduce women’s capacity to access and understand health information and address the health information needs of socioeconomically disadvantaged women.